Adolescentes preocupadas em conquistar um corpo magro: Um estudo sobre discursos produzidos em diários eletrônicos - Souto, Maria Elisa Magalhães Albuquerque (2006)
The concern about a good physical condition is heavily present nowadays, in documentary films about health and in the media, and it is also expressed through the outstanding growth of physical academies, beauty institutes and aesthetic medicine and all kind of aesthetic surgeries. In the western world the body wave is a significant trend, characterized by the great investments in body image. However, what is overlooked is the fact that in parallel trend grows the number of teenagers, especially females, with all kind of problems related to their body image. As adolescence is a moment of transformations, teenagers tend to be more aware of their body image and often neglect food ingestion and try to build their bodies following the images they have from top models and movie stars. The low self-esteem accompanying this sort of experience is an additional problem. Therefore the research aim to analyze discourses regarding the body image produced in world wide web diaries (blogs). The blogs selection was made through the site www.blogs.com.br, which is considered the widest guide of electronic diaries in Brazil. We looked after blogs including the keyword body and from adolescents aged 10 to 19, who showed concern about a slim body. Three blogs were chosen, considering the example criteria. Discourse analysis shows that these teenagers feel unsatisfied with their bodies, searching by all means the thinness presented as a aesthetic paradigm in western societies which often implies neglecting their own health, using appetite inhibitor drugs, restricting or totally abstaining food ingestion for long periods of time, or provoking themselves vomits after ingesting food. These behaviors, together with intense fear of gaining weight, can be characterized as alimentary disorders, related to the body image. As they usually hide this sort of behaviors from family and friends who do not share this concern, the blogs seem to be an easy tool for adolescents to find peers with whom to share common values and ideas and reaffirm their identities and virtual sense of community